Short‐term effectiveness of a web‐based tailored intervention for cancer survivors on quality of life, anxiety, depression, and fatigue: randomized controlled trial. Issue 2 (14th March 2016) - Willems, Roy A.; Bolman, Catherine A. W.; Mesters, Ilse; Kanera, Iris M.; Beaulen, Audrey A. J. M.; Lechner, Lilian
Abstract: Background: The aim of this study was to evaluate the short‐term effectiveness of the web‐based computer‐tailored intervention Kanker Nazorg Wijzer (Cancer Aftercare Guide). The intervention aims to support cancer survivors with managing psychosocial and lifestyle‐related issues. In this study, the impact on quality of life, anxiety, depression, and fatigue were evaluated. Methods: Cancer survivors were recruited through 21 Dutch hospitals (November 2013–June 2014). Outcome measures included quality of life (European Organization for Research and Treatment of Cancer Quality of Life Questionnaire‐C30), anxiety and depression (Hospital Anxiety and Depression Scale), and fatigue (Checklist Individual Strength). In a randomized controlled trial with an intervention group ( n = 231) and a waiting list control group ( n = 231), the short‐term effectiveness was evaluated through multilevel linear regression analyses, controlling for selective dropout, baseline differences, and several demographic and disease‐related characteristics. Results: In total, 188 participants of the intervention group and 221 of the control group completed the 6‐month measurement (dropout = 11.5%). The intervention was effective in reducing depression ( B = −0.63, p = 0.007, f 2 = 0.019, d = 0.21) and fatigue ( B = −4.36, p = 0.020, f 2 = 0.013, d = 0.21). In addition, effects were found for emotional ( B = 3.47, p = 0.022, f 2 = 0.013, d = 0.15) and social functioning ( B = 3.95, p = 0.011, f 2 = 0.017, d = 0.15), although this evidence was less strong. There were indications that the effects of fatigue and social functioning were influenced by module use. Conclusions: While effect sizes were small, they can be considered as clinically relevant. With the Cancer Aftercare Guide being an effective, low‐intensive, and easy accessible intervention, it could serve as a first step in stepped care for needs assessment and initial support for psychosocial problems that are present after cancer treatment. Copyright © 2016 John Wiley & Sons, Ltd.